Clinical and microbiological study of paediatric infectious keratitis in South India: a 3-year study (2011–2013). Issue 12 (25th February 2016) - Aruljyothi, Lokeshwari; Radhakrishnan, Naveen; Prajna, Venkatesh N; Lalitha, Prajna
Abstract : Purpose: To study the risk factors, microbiological profile and clinical outcomes of infectious keratitis affecting paediatric patients. Study design: Retrospective case series. Methods: Review of case records of paediatric patients (0–16 years) diagnosed with infectious keratitis who presented to Aravind Eye Hospital, Madurai, India during January 2011 to December 2013. Demographic details, predisposing factors, microbiological investigations, clinical course and visual outcome were analysed. Results: In this time period, 240 eyes of 234 children had a diagnosis of infectious keratitis. One hundred and twenty-five (53.4%) children had a history of trauma. Smears were obtained in 220 eyes, while culture was performed in 191 eyes. The culture results were positive in 142 (74.3%) eyes. Fungi was the most common infectious agent isolated in culture (54.2%) followed by bacteria (40.8%) and acanthamoeba (2.1%). Successful healing of the keratitis with appropriate medical therapy occurred in 223 (92.9%) eyes, while 17 (7.1%) eyes required therapeutic keratoplasty. Of the 151 patients with preliminary and final visual acuity, vision improved by 2 lines in 68 eyes (45%), stayed the same in 75 eyes (49.6%) and worsened in 8 eyes (5.3%). Conclusions: Contrary to previous reports, fungi are the most common aetiological organism in the causation of infectious keratitis in children in our study population. Fusarium was the most common fungal species isolated. These data are similar to the data obtained from adult patients with infectious keratitis in this region. While microbiological investigations are important to initiate appropriate antimicrobial therapy, the findings from our study need to be kept in mind, especially while initiating empirical therapy in this population.